If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.6x + 22 = 28 Reorder the terms: 22 + 0.6x = 28 Solving 22 + 0.6x = 28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + 0.6x = 28 + -22 Combine like terms: 22 + -22 = 0 0 + 0.6x = 28 + -22 0.6x = 28 + -22 Combine like terms: 28 + -22 = 6 0.6x = 6 Divide each side by '0.6'. x = 10 Simplifying x = 10
| 5.4X+.4=3.4 | | 7x+3-(2x-1)= | | 14y-8-10y=0 | | (Y-2)+y=18 | | .6k-.1k=.5k-1 | | x^5-3x^4+4x^3-8x^2+16=0 | | ln(6x-6)=13 | | 4-(x+9)=-x-4-5 | | -4s=-34 | | n-5*2=5 | | 8y^2+36y-72=0 | | 6-(-8)=0 | | 11m+3=8m-18 | | 575=35x-75y | | 2(b-5)=5(b+5)-17 | | 2(y+3)=2y-6(y+5) | | m^2+3=0 | | 5m-3=2(m+3) | | x^2+72=17x | | 35x+50y= | | 162+16m=354 | | 15x^2-10x+15=0 | | 15x^2-10x+15=0 | | 14-7t-16=8t+25-6t | | 4m^2+9=0 | | 4(1h+2)=3(h-2) | | 6x+3-2x=2x+7 | | -12m-3=-12 | | -70-3x+x^2=0 | | 5y+40=-2y-9 | | -0.5m=-9 | | 28n-54=450 |